PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP KUALITAS LABA PADA PERUSAHAAN SEKTOR INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI - Prastion Syah Putra; Mike Kusuma Dewi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2023)
This research aims to examine the influence of capital structure and liquidity on earnings quality of infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange from 2018 to 2021. The research uses a quantitative research method with panel data. The data source used in this study is secondary data. The secondary data used in this study were financial statements of basic industry and chemical manufacturing companies listed on the Indonesia Stock Exchange, obtained through links from http://www.idx.co.id and http://idnfinancials.com, as well as other related websites. The population of this study is infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange from 2018 to 2021, totaling 70 companies. The sampling technique used in this article is purposive sampling with a sample size of 18 companies, for a total of 72 company data over a four-year period. The results of the research indicate that earnings growth does not significantly affect earnings quality, while liquidity has a significant effect on earnings quality. These results were obtained through data analysis using EVIEWS9.